PHYSICOCHEMICAL PROPERTIES AND MINERAL COMPOSITION OF HONEY (Apis mellifera) FROM NORTH CENTRAL NIGERIA - N. C. Ikegbunam; J. W. Okwong; A. C. Anukwuorji (The Bioscientist)
This study evaluated the nutritional quality and potential adulteration of six honey samples obtained from Benue and Kogi States by analyzing their moisture content, ash content, fat content, protein content, hydroxymethylfurfural (HMF), free acidity, pH, polyphenol content, heavy metals, and mineral composition. Standard analytical methods were used for evaluation. The pH values of the samples ranged from 3.95 to 4.30, with free acidity between 2.72±0.10 and 57.40±0.81 meq/kg. The ranges of values of the other tested parameters in the samples are as follows: moisture content (8.35±0.33 to 10.34±0.02%), ash content (0.19±0.01 to 0.86±0.01%), fat content (0.00±0.00 to 0.54±0.03%), protein content (0.28±0.01 to 0.56±0.02%), polyphenol content (3.75±0.72 to 90.12±0.07%) and HMF (16.13±2.62 to 66.77±6.78 mg/kg). Cadmium and Lead were not detected. The mineral concentrations were as follows: sodium (1.80±0.06 to 9.75±0.14 mg/100 g), potassium (12.89±0.03 to 27.62±0.02 mg/100 g), calcium (3.55±0.20 to 9.50±0.23 mg/100 g), magnesium (2.00±0.06 to 7.60±0.17 mg/100 g), and zinc (2.15±0.09 to 4.10±0.06 mg/100 g). The nutritional quality of these honey samples is supported by their high carbohydrate content, metabolizable energy, low crude fat content, and significant levels of essential minerals, which make them suitable for use in various food products.